Optimal Network Reconfiguration Incorporating with Renewable Energy Sources in Radial Distribution Networks - Mohammed Hamouda Ali, Mohammed Mehanna, Elsaied Othman (International Journal of Advanced Science and Technology, 2020)
The Distribution system reconfiguration (DSR) is one of the facile, cheapest and most powerful ways to reduce operational losses and enhance voltage profile. This paper also has deemed renewable distributed generations (RDGs) in the distribution network (DN). Distribution network reconfiguration (DNR) is considered an intricate combinatorial problem that needs radially fulfilment. In addition, the wrong selection of DG impacts directly on the distribution system (DS) and primarily increased the voltage perversion and power losses. Therefore, a combination of DNR and DG technologies is deemed the best solution to improve the imperfections of the radial distribution network (RDN) at the lowest cost. DNR problem is a nonlinear combination problem that makes it impossible to solve by mathematical computation methods. Therefore, using metaheuristic algorithms is the ideal method as they are easy to execute and lead to very rapid convergence. Simulated annealing (SA) technique has been executed here effectively to better voltage profile and lessens real power loss simultaneously. This article contributes to computations reduction and feasible search space lowering by the proposed explicit radially verification. Modified particle swarm optimization (MPSO) and SAMPSO have been presented for the first time to achieve the objective function. Backward Forward Sweep (BFS) approach has been hired for load flow calculations as a simulation tool to analyze the network performance considering the constraints. These algorithms have been exploited in three techniques DSR, DG and DSR-DG and tested in IEEE 33 & 69 bus and the test results manifested that these algorithms are efficacious and proper for wide-ranging applications.